The Potential Role of Bioactive Plasmalogens in Lung Surfactant - Zhuo, Ruijiang; Rong, Pu; Wang, Jieli; Parvin, Rokshana; Deng, Yuru (Frontiers in Cell and Developmental Biology, 2021)
Neonatal respiratory distress syndrome (NRDS) is a type of newborn disorder caused by the deficiency or late appearance of lung surfactant, a mixture of lipids and proteins. Studies have shown that lung surfactant replacement therapy could effectively reduce the morbidity and mortality of NRDS, and the therapeutic effect of animal-derived surfactant preparation, although with its limitations, performs much better than that of protein-free synthetic ones. Plasmalogens are a type of ether phospholipids present in multiple human tissues, including lung and lung surfactant. Plasmalogens are known to promote and stabilize non-lamellar hexagonal phase structure in addition to their significant antioxidant property. Nevertheless, they are nearly ignored and underappreciated in the lung surfactant-related research. This report will focus on plasmalogens, a minor yet potentially vital component of lung surfactant, and also discuss their biophysical properties and functions as anti-oxidation, structural modification, and surface tension reduction at the alveolar surface. At the end, we boldly propose a novel synthetic protein-free lung surfactant preparation with plasmalogen modification as an alternative strategy for surfactant replacement therapy.